Precepting nurse practitioner students: A new view—Results of two national surveys of nurse practitioner preceptors. Issue 8 (26th June 2017) - Roberts, Mary Ellen; Wheeler, Kathy J.; Tyler, Diane O.; Padden, Diane L.
Abstract: Purpose: The aim of two national studies was to identify characteristics of nurse practitioners (NPs) who precept and the benefits, incentives, and barriers associated with the NP preceptor role. Methods: Stratified randomized sampling was used to invite a representative number of NPs from each state to participate in a 2015 survey and a follow‐up survey in 2016. These descriptive, exploratory studies distributed electronic questionnaires to 5000 randomly selected NPs in the 2015 survey and 40, 000 NPs in the 2016 survey. Responses from 10.9% ( n  = 548) and 9.9% ( n = 3970),  respectively, were analyzed. Conclusions: The findings show strong support among our NP colleagues to assist with educating future NPs. Several benefits, barriers, and motivators among stakeholders were identified that need to be considered when working with preceptors. Implications for practice: This study provides a basis for understanding the current climate in education when working with clinical preceptors. Many areas become apparent where NP education could enhance the experience for both the student and the preceptor. Educational settings need to consider preceptor time, issues with online learning, and the rise of specialty practices. Offering incentives linked to the most valued, positive aspects of the role and methods to overcome barriers should be explored.